Electrofishing Encounter Probability, Survival, and Dispersal of Stocked Age‐0 Muskellunge in Wisconsin Lakes. (20th March 2020) - Dembkowski, Daniel J.; Kerns, Janice A.; Easterly, Emma G.; Isermann, Daniel A.
Abstract: Boat electrofishing is often used to sample age‐0 Muskellunge Esox masquinongy for indexing recruitment or evaluating stocking success. However, electrofishing samples typically result in low CPUE, prompting concerns regarding whether catch rates reflect actual abundance or whether boat electrofishing is generally ineffective for capturing age‐0 Muskellunge (i.e., if fish are not being encountered by the gear). To address these concerns, we used radiotelemetry to evaluate the probability of encountering stocked age‐0 Muskellunge (230–350 mm TL) during standardized fall electrofishing surveys in three Wisconsin lakes. Our approach also allowed us to evaluate short‐term survival and dispersal from stocking locations. Despite limited dispersal (<2.5 km) from the stocking locations and relatively high short‐term survival (75–94%) of radio‐tagged fish, few age‐0 Muskellunge were located within the path of the electrofishing boat (7–30%). Furthermore, the probability of encounter by boat electrofishing varied by as much as 6.3 times among lakes. Differences in encounter probability among lakes appeared to be related to lake basin and habitat characteristics. Overlays of electrofishing sampling effort and fish locations revealed that traditional shoreline electrofishing may not be an effective way of estimating age‐0 Muskellunge CPUE. Modifications to electrofishing protocols, including increased effort in offshore areas and consideration of basin characteristics and habitat, may be needed to increase encounter probabilities and the utility of boat electrofishing for sampling age‐0 Muskellunge.